The evolution of Dircom: from communication manager to reputation strategist (Communication & Society, 2013)
This paper has two objectives. First, it attempts to show the evolutionof companies in the management of intangibles: brand, communication, CSR, etc. Furthermore, it aims to define the current framework of corporate reputation. In the development of the paper, in addition to literature sources, in-depth interviews have been used with executives of pioneer companies in the implementation of corporate reputation. Interviews were also directed specifically towards experts in the management of intangibles. The conclusion is that a holistic management of intangibles is now necessary and proposes an evolution of the Dircom towards a new role: Chief Communication and Reputation Officer or Chief Reputation Officer, as a corporate reputation strategist.